Manajemen Dakwah Di Taman Kanak-Kanak - Faridatul Jannah; Desi Endang Maisuri; Mumun Mulyati (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this research is to describe the management of preaching carried out in Kindergarten. The research method is qualitative with a library study approach. Data collection techniques with documentation studies. Data processing techniques with reduction, presentation and conclusion drawing. The results showed: (1) management is an arrangement made by someone before doing work. (2) da'wah is an invitation made by someone to other people to do good. (3) Kindergarten is an educational institution whose students are 2-6 years old. (4) the management of preaching in Kindergarten, first of planning da'wah about planning methods and materials of preaching. The second is the organization of da'wah, namely the division of da'wah tasks in class. The third is the implementation of da'wah by paying attention to the facilities and infrastructure of giving da'wah in class. The fourth control of da'wah is by paying attention to the smooth implementation of da'wah in the classroom. The fifth evaluation of da'wah is by assessing the implementation and results of da'wah in class.